2018
DOI: 10.1042/bcj20170913
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-9 CARD : core domain interactions require a properly formed active site

Abstract: Caspase-9 is a critical factor in the initiation of apoptosis, and as a result is tightly regulated by a number of mechanisms. Caspase-9 contains a Caspase Activation and Recruitment Domain (CARD), which enables caspase-9 to form a tight interaction with the apoptosome, a heptameric activating platform. The caspase-9 CARD has been thought to be principally involved in recruitment to the apoptosome, but its roles outside this interaction have yet to be uncovered. In this work we show that the CARD is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 63 publications
(86 reference statements)
3
21
0
Order By: Relevance
“…24 Caspase-9 is the upstream caspase which is involved in the apoptotic process. [25][26][27] In the current study, we observed that the activities of caspase-3 and caspase-9 proteins induced, these findings suggested that Res increased the apoptosis of HSC-3 cells via increasing the activities of caspase-3 and caspase-9.…”
Section: Discussionsupporting
confidence: 64%
“…24 Caspase-9 is the upstream caspase which is involved in the apoptotic process. [25][26][27] In the current study, we observed that the activities of caspase-3 and caspase-9 proteins induced, these findings suggested that Res increased the apoptosis of HSC-3 cells via increasing the activities of caspase-3 and caspase-9.…”
Section: Discussionsupporting
confidence: 64%
“…5b and Supplementary Fig. 5) 60 . We then used wildtype caspase-9 monomer C and inactive monomer I to assemble homo-and heterodimeric DNA nanostructures, and confirmed that the heterodimeric variants assembled correctly using agarose gel electrophoresis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…As such, several features of the native system that could modulate caspase-9 activation and regulation are not taken into account. For example, recent work has indicated that allosteric interactions of the catalytic domain of caspase-9 with its CARD, the flexible linkers, and the apoptosome itself can affect enzyme activity 36,53,54 . However, we argue that a modular DNA-based model system composed of a controlled number of catalytic domains with well-defined interactions can help isolate the key molecular determinants of caspase-9 regulation.…”
Section: Dna Origami-mediated Caspase-9 Enzyme Activitymentioning
confidence: 99%